Cut‐offs for defining uterine prolapse using transperineal ultrasound in Chinese women: prospective multicenter study. (1st July 2021) - Wu, M.; Wang, X.; Lin, X.; Fu, Y.; Chen, H.; Guan, X.; Huang, W.; Chen, Y.; Zhang, L.; Jing, C.; Wei, J.; Tian, J.; et al.
ABSTRACT: Objective: Transperineal ultrasound is a simple and highly repeatable method that has been used increasingly in the quantification of pelvic organ prolapse, but abnormal uterine descent on ultrasound in Chinese women is still poorly defined. We aimed to determine the optimal cut‐off to define abnormal uterine descent on transperineal ultrasound in Chinese women. Methods: This prospective multicenter study recruited women who were examined in tertiary‐level gynecological centers, due to symptoms of lower urinary tract and/or pelvic floor dysfunction, between February 2017 and September 2018. All recruited women underwent a standardized interview, pelvic organ prolapse quantification (POP‐Q) examination, and four‐dimensional transperineal ultrasound examination. On ultrasound, uterine descent was measured relative to the posteroinferior margin of the symphysis pubis during maximum Valsalva maneuver. The optimal cut‐off value for definition of abnormal uterine descent was selected as the value with the highest Youden index and the diagnostic performance of this cut‐off for the prediction of prolapse symptoms and POP‐Q stage was assessed and compared by means of the area under the receiver‐operating‐characteristics curve (AUC). Results: In total, 538 Chinese women, with a mean age of 39.4 (range, 18–81) years, were enrolled into the study. Both uterine descent on transperineal ultrasound ( P < 0.001) and POP‐Q stage ( P < 0.001) were associated strongly with presence of prolapse symptoms. Uterine descent on ultrasound was associated significantly with POP‐Q stage for apical compartment prolapse ( P < 0.001). The optimal cut‐off value for the definition of abnormal uterine descent on transperineal ultrasound during maximum Valsalva maneuver in the prediction of prolapse symptoms was 4.79 mm above the symphysis pubis (AUC, 0.75 (95% CI, 0.71–0.78)), while the optimal cut‐off values in the prediction of prolapse of POP‐Q Stage ≥ 1 and POP‐Q Stage ≥ 2 were 6.63 mm above the symphysis pubis (AUC, 0.83 (95% CI, 0.80–0.86)) and 8.42 mm below the symphysis pubis (AUC, 0.85 (95% CI, 0.82–0.88)), respectively. Conclusions: The optimal cut‐off value to define abnormal uterine descent on transperineal ultrasound during maximum Valsalva maneuver for the prediction of prolapse symptoms in this population of Chinese women was 4.79 mm above the symphysis pubis, close to that for predicting apical compartment prolapse of POP‐Q Stage ≥ 1 (6.63 mm above the symphysis pubis). These are somewhat different from values described previously in mainly Caucasian populations. Ethnic differences should be taken into account in the evaluation of pelvic organ prolapse using transperineal ultrasound. © 2020 International Society of Ultrasound in Obstetrics and Gynecology